Representasi Nilai Moral dalam Film Bolehkah Sekali Saja Kumenangis: Analisis Semiotika Roland Barthes - Putri, Icha Amaliyah; Wulandari, Yulianti Fajar; Hamid, Ali Imron (Comit: Communication, Information and Technology Journal, 2025)
This study uses Roland Barthes' semiotic approach to investigate the representation of moral values in the movie Boleh Boleh Sekali Sekali Kumenangis. The movie contains relevant social issues such as emotional trauma, family conflict, and courage to face the pressure of patriarchal culture. This is the reason why this movie was chosen. Semiotic analysis was used, with an emphasis on denotative, connotative, and mythical meanings that appear in the visual story, dialog, and gestures of the characters. The research shows that the visual symbols, character changes, and internal conflict dynamics show moral values such as courage, emotional honesty, and responsibility. Tari, the main character, serves as a representation of women's courage to break the chain of domestic violence, and her father serves as a representation of self-awareness to admit mistakes. The results show that movies can be an effective tool for teaching morals and also a place for social thinking. This study reaches the conclusion that Barthes' semiotic approach is relevant to examine films as ideological and non-neutral cultural products. It is hoped that this study will become a reference for the study of film, communication, and character education in Indonesia.